Rapid onset sodium appetite and orofacial responses to intraoral capsaicin and hypertonic NaCl in the rat - Fernandes, Natalie Aparecida Rodrigues [UNESP]; Santos, Bruna Maitan [UNESP]; Andrade-Franzé, Gláucia Maria Fabrício de [UNESP]; de Paula, Patrícia Maria [UNESP]; Andrade, Carina Aparecida Fabrício de [UNESP]; Vanderlei Menani, José [UNESP]; De Luca, Laurival Antonio [UNESP] (Elsevier, 2022)
Sodium appetite reverts from aversive to hedonic the orofacial responses to intraoral hypertonic NaCl in a taste reactivity test (TRT). An electrophysiological-based hypothesis suggests that aversion to salty taste results from oral nociception (e.g., like that produced by intraoral capsaicin). In the present work, we used the TRT to investigate whether sodium appetite and its sensitization produce similar effects on the orofacial responses to the intraoral infusion of either capsaicin or hypertonic NaCl. We produced rapid onset sodium appetite by subcutaneous injection of furosemide combined with a low dose of captopril (Furo/Cap) in adult rats instrumented with intraoral cannula. Then, the animals had 1-h free access to water (thirst test). Immediately after, they entered the TRT receiving a first intraoral infusion (1 ml for a total of 1 min) of (0.5 μM) capsaicin and, 20 min later, a second one of (0.3 M) NaCl. The sequence, Furo/Cap injection - thirst test - TRT, was repeated twice more every three days. The repetition of the Furo/Cap increased the frequency of hedonic responses, decreased the frequency of aversive responses, and increased the hedonic:neutral response ratio to NaCl. The repetition of Furo/Cap reduced transiently the neutral orofacial responses and ended decreasing the aversive:neutral response ratio to capsaicin. The results suggest that repeated Furo/Cap sensitizes the palatability of hypertonic NaCl. They also suggest that sensitization of sodium appetite involves increased sodium “liking”. Finally yet importantly, we found that sensitization of sodium appetite can influence orofacial responses to capsaicin. Rapid onset sodium appetite and orofacial responses to intraoral capsaicin and hypertonic NaCl in the rat.
Keywords: Emotion; Oral nociception; Salt intake; Taste; “Liking”